Development of an ELISA as a complement to MAT for swine leptospirosis diagnosis - Micaela Esteban; Cristina Sanchez; Marcelo A. Rodriguez; Vanina R. Saraullo; Micaela Hamer; Bibiana F. Brihuega; Luis Samartino; Mara L. Martinez (Research in Veterinary Science, 2026)

MFC 5.0: An exascale many-physics flow solver - Benjamin Wilfong; Henry A. Le Berre; Anand Radhakrishnan; Ansh Gupta; Daniel J. Vickers; Diego Vaca-Revelo; Dimitrios Adam; Haocheng Yu; Hyeoksu Lee; Jose Rodolfo Chreim; Mirelys Carcana Barbosa; Yanjun Zhang; et al. (Computer Physics Communications, 2026)

Seasonal Predictions and Their Applications in the Mediterranean Region: Part II—Prediction‐Based Services - Silvio Gualdi; Ernesto Rodriguez Camino; Esteban Rodriguez Guisado; Andrea Toreti; Massimiliano Pasqui; Constantin Ardilouze; Wafae Badi; Lauriane Batté; Fatima Driouech; Kristina Fröhlich; Javier García‐Serrano; Silvia Terzago; et al. (International Journal of Climatology, 2026)
This review paper examines the development and application of climate predictions, primarily at seasonal timescales, as actionable information for decision‐making, with a specific focus on the Mediterranean region. It illustrates and analyses the steps required to transform climate model probabilistic forecasts into user‐defined information, emphasising the iterative nature of climate service development. By leveraging tools such as bias adjustment, downscaling, probabilistic calibration and impact models, these services provide tailored solutions to key sectors including energy, water supply, transport and agriculture. The paper discusses the contributions of global initiatives, such as the Global Framework for Climate Services (GFCS), and EU‐funded projects like EUPORIAS, MEDSCOPE and MED‐GOLD, which have advanced sector‐specific applications of climate predictions in the region. These initiatives illustrate how tailored climate services can address critical challenges ranging from renewable energy planning to drought risk mitigation and agricultural yield forecasting. The review highlights persistent challenges, including limited forecasting skill in the Mediterranean area, data accessibility issues and the need for robust impact‐based verification. To enhance the uptake and effectiveness of climate services, the review recommends fostering interdisciplinary collaboration, promoting iterative co‐production with users, improving the communication of uncertainty and forecast skill, and ensuring the sustainability of services beyond project lifetimes. This work underscores the potential of climate services to enhance resilience in the Mediterranean region, bridging the gap between scientific advances and practical applications.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Seasonal Predictions and Their Applications in the Mediterranean Region: Part I—Sources of Predictability and Prediction Skill - Silvio Gualdi; Javier García‐Serrano; Constantin Ardilouze; Silvia Terzago; Veronica Torralba; Wafae Badi; Lauriane Batté; Fatima Driouech; Kristina Fröhlich; Ernesto Rodriguez Camino; Esteban Rodriguez Guisado; Massimiliano Pasqui; et al. (International Journal of Climatology, 2026)
The capability to predict climate fluctuations from sub–seasonal–to–decadal timescales would yield large and significant socio–economic benefits. On the other hand, our limited understanding of the mechanisms and processes responsible for predictability and systematic model errors hampers our ability to simulate and forecast climate variability. As a result, current forecast quality remains relatively unsatisfactory, particularly in the mid‐latitudes and in the Mediterranean basin. In recent years, several research studies and collaborative projects have been conducted in order to improve the skill of forecasting systems and the quality of the data and climatic information they produce. This effort has led to substantial advancements in understanding Mediterranean climate variability and its drivers, as well as to improvements in the capability to provide reliable climate predictions for this region. The main objective of this paper is to review and discuss the current understanding of climate variability and sources of predictability in the Mediterranean basin and surrounding areas, to assess the current capability of climate prediction systems in order to provide skilful predictions in this region to feed services in relevant socio‐economic sectors. Examples of advanced tools and innovative methodologies recently developed to enhance predictions, both in terms of forecast skill and of the quality of the data they provide (e.g., sub–sampling and bias correction), will also be discussed.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Reduction of frosty pod rot severity in Theobroma cacao CCN51 by indigenous Trichoderma-based bioformulations under controlled conditions - Anthony Apolinario Cortez-Lázaro; Ramiro Esteban Rodriguez; Ingrid Milagros Iliquin-Inga; Jorge Ronny Diaz-Valderrama; Santos Triunfo Leiva-Espinoza; Edwin Hualpa-Cutipa; Segundo Manuel Oliva-Cruz; Liz Marjory Cumpa-Velasquez (Fungal Biology, 2026)

Correction to: The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2026)

Reconstructing ocean-atmosphere interactions in La Guajira upwelling system through organic and mineral proxies over the past 1800 years - Aura María Rodriguez-Burgos; Francisco Javier Briceño-Zuluaga; Heitor Evangelista; Valentina Flores-Aqueveque; Juliana Nogueira; Alexis Castillo; William Esteban Quiroga-Camargo; Mercedes Mendez-Millan; Abdelfettah Sifeddine (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Use of shotgun immunoproteomics for the development of protein vaccines against Edwardsiella piscicida - Kim L. Jacobsen; Matt J. Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Cynthia C. Ware; Fernando Y. Yamamoto; Noor-ul Huda; Tania Rodriguez-Ramos; Brian Dixon; et al. (Fish & Shellfish Immunology, 2026)

The MiniBond test: A robust and cost-effective alternative for ore hardness characterisation and geometallurgical profiling - Diego Mesa; Patricio Berríos; Esteban Rodriguez; Caillan Govender; Portia Mudau; Sergio Spichiger; Roger Amelunxen; Peter Amelunxen (Minerals Engineering, 2025)

Validation of pharmacokinetic model for quizartinib quantified by UPLC-MS/MS in patients with FLT3-ITD negative newly diagnosed acute myeloid leukemia - Antonio Solana-Altabella; Carles Iniesta-Navalón; Maria Chovi-Trull; Rebeca Rodriguez-Veiga; Marina Lopez-Nogueroles; David Martínez-Cuadrón; Mayte Gil-Candel; Laura Torres-Miñana; Evelyn Acuña-Cruz; Isabel Cano-Ferri; Blanca Boluda; Irene Navarro-Vicente; et al. (European Journal of Clinical Pharmacology, 2025)
Purpose Quizartinib pharmacokinetics in FLT3-ITD negative acute myeloid leukemia (AML) remain largely unexplored. This study aims to validate a population pharmacokinetics model (popPK) for quizartinib in plasma samples of FLT3-ITD negative AML patients. To do so, an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for the quantification of quizartinib. Methods Plasma samples were collected from FLT3-ITD negative newly diagnosed AML patients undergoing quizartinib therapy at induction in the QUIWI phase II clinical trial [NCT04107727, PETHEMA group] between March 2020 and February 2022. The UPLC-MS/MS method was developed and validated. A previously described popPK model was validated using external validation techniques and implemented using the software NONMEM v7.5. Results The developed UPLC-MS/MS method demonstrated high accuracy and precision with a linear range of 6 to 200 ng/mL, with relative standard deviation between 3–11 and accuracy of 88–97% from nominal values. The external validation of the quizartinib popPK model showed minimal bias at the population level (MdPE: -9.86%; ME: 0.50 ng/mL, p = 0.964), but moderate imprecision (MdAPE: 32.28%) and suboptimal accuracy (F20: 24.5%; F30: 43.4%). Individual predictions improved performance, with negligible bias (MdPE: -0.50%), acceptable precision (MdAPE: 11.27%), and F20 (64.2%) and F30 (77.4%) exceeding predefined thresholds. Visual predictive checks confirmed adequate prediction of median concentrations, though some deviations occurred at extremes. Conclusion This study presents a replicable UPLC-MS/MS method for the determination of quizartinib in plasma. The validated popPK model can be used to optimize dosing strategies in future clinical studies.

Linking within-host immune dynamics to between-host transmission and reinfection risk - Rodolfo Blanco-Rodriguez; Alejandro Anderson; Esteban Hernandez-Vargas (Journal of Theoretical Biology, 2025)

Dynamic WNT signaling controls differentiation of hematopoietic progenitor cells from human pluripotent stem cells - Mo Li; Keiichiro Suzuki; Mengge Wang; Christopher Benner; Manching Ku; Li Ma; Ladan Kobari; Na Young Kim; Nuria Montserrat; Chan-Jung Chang; Guanghui Liu; Jing Qu; et al. (Science China Life Sciences, 2025)

Splenomegaly, Spleen Amyloidosis and Neutrophil Infiltration are Present in 3xTg-AD, but not Tg-SwDI Mice - Gonzalo Acero; Adrian Rodriguez-Lopez; Georgina Díaz; Daniel Esteban; Mónica Herrera-Ángeles; Goar Gevorkian (NeuroMolecular Medicine, 2025)
It is now widely accepted that the development of neurodegenerative diseases depends on and affects many pathological processes, both in the brain and the periphery. Inflammatory, cardiovascular, metabolic, cerebrovascular, autoimmune, and other environmental factors have been extensively studied and shown to contribute notably to the onset, pathogenesis, and clinical outcome of Alzheimer´s disease (AD), Parkinson´s disease (PD), cerebral amyloid angiopathy (CAA), multiple sclerosis, and other neurological disorders. Likewise, AD-induced changes in other tissues outside the central nervous system, such as abnormalities observed in the liver, spleen, or lungs, have been documented and extensively studied, leading to a better understanding of brain-periphery crosstalk in neurodegenerative diseases and the development of novel diagnostic and therapeutic approaches. In this study, we documented striking differences in the periphery in two frequently used, well-established APP transgenic mouse models of AD: 3xTg-AD mice, harboring three human genes (APP, tau, and Psen1), and Tg-SwDI mice, expressing human APP with the Swedish and vasculotropic Dutch/Iowa mutations in the brain. We documented splenomegaly, immunoglobulin-associated spleen amyloidosis, and an increase in the percentage of neutrophils in the spleen and macrophages in the liver in 3xTg-AD mice but not in age-matched Tg-SwDI mice, which are commonly used as an AD/CAA model. Our data suggest that the results observed in any transgenic mouse strain should be taken into account with caution. A detailed knowledge of pathological characteristics recapitulated in a particular strain can help to determine which mice are more appropriate for studying a specific mechanism or therapeutic approach.

Consequential life cycle assessment of pretreatment strategies for a microalgae-based wastewater treatment pilot unit in a circular livestock industry bioeconomy - Anaid López-Sánchez; Carlos Daniel García-López; Gary Ossmar Lara-Topete; Juan Daniel Castanier-Rivas; Paloma Barajas-Álvarez; Martín Esteban González-López; Ana Laura Silva-Gálvez; Hongying Zhou; Christopher Q. Lan; Carlos Eduardo Robles-Rodriguez; Samir Meramo-Hurtado; Misael Sebastián Gradilla-Hernández (Algal Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Phthalates and substitute plasticizers: Main achievements from the European human biomonitoring initiative HBM4EU - Antje Gerofke; Rosa Lange; Nina Vogel; Phillipp Schmidt; Till Weber; Madlen David; Hanne Frederiksen; Kirsten Baken; Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Žanna Martinsone; et al. (International Journal of Hygiene and Environmental Health, 2024)

Crustal structure of the Western Azuero Peninsula, Panama: Insights into the structure of accretionary complexes and forearc ophiolites - Carolina Ortiz-Guerrero; Camilo Montes; David W. Farris; Catalina Agudelo; Margarita Ariza Acero; Juliana Ayala; Jose David Avellaneda; Alejandro Cortes-Calderon; Esteban Gaitan; Sebastian Garzon; Daniel Gongora-Blanco; Nubia Andrea Jara; et al. (International Geology Review, 2024)

HBM4EU-MOM: Prenatal methylmercury-exposure control in five countries through suitable dietary advice for pregnancy – Study design and characteristics of participants - Andromachi Katsonouri; Catherine Gabriel; Marta Esteban López; Sonia Namorado; Thorhallur I. Halldorsson; Janja Snoj Tratnik; Laura Rodriguez Martin; Achilleas Karakoltzidis; Anthoula Chatzimpaloglou; Despina Giannadaki; Elena Anastasi; Anthi Thoma; et al. (International Journal of Hygiene and Environmental Health, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Human urinary arsenic species, associated exposure determinants and potential health risks assessed in the HBM4EU Aligned Studies - Jurgen Buekers; Kirsten Baken; Eva Govarts; Laura Rodriguez Martin; Nina Vogel; Marike Kolossa-Gehring; Zdenka Šlejkovec; Ingrid Falnoga; Milena Horvat; Sanna Lignell; Anna Karin Lindroos; Loïc Rambaud; et al. (International Journal of Hygiene and Environmental Health, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Deprescribing of non-antiretroviral therapy in HIV-infected patients - José-Ramón Blanco; Ramón Morillo; Vicente Abril; Ismael Escobar; Enrique Bernal; Carlos Folguera; Fátima Brañas; Mercedes Gimeno; Olatz Ibarra; José-Antonio Iribarren; Alicia Lázaro; Ana Mariño; et al. (European Journal of Clinical Pharmacology, 2020)

Blood Flow-Restricted Training in Older Adults: A Narrative Review - Abel Plaza-Florido; Jairo H. Migueles; Antonio Piepoli; Pablo Molina-Garcia; Maria Rodriguez-Ayllon; Cristina Cadenas-Sanchez; Jose Mora-Gonzalez; Irene Esteban-Cornejo; Francisco B. Ortega (Journal of Science in Sport and Exercise, 2020)

Terpinen-4-ol and carvacrol affect multi-species biofilm composition - Patricia Milagros Maquera Huacho; Esteban Rodriguez Herrero; Tim Verspecht; Martine Pauwels; Elcio Marcantonio; Denise Madalena Palomari Spolidorio; Wim Teughels (Biofouling, 2019)

The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2019)
Cerebral preconditioning (PC) confers endogenous brain protection after stroke. Ischemic stroke patients with a prior transient ischemic attack (TIA) may potentially be in a preconditioned state. Although PC has been associated with the activation of pro-survival signals, the mechanism by which preconditioning confers neuroprotection is not yet fully clarified. Recently, we have described that PC-mediated neuroprotection against ischemic insult is promoted by p53 destabilization, which is mediated by its main regulator MDM2. Moreover, we have previously described that the human Tp53 Arg72Pro single nucleotide polymorphism (SNP) controls susceptibility to ischemia-induced neuronal apoptosis and governs the functional outcome of patients after stroke. Here, we studied the contribution of the human Tp53 Arg72Pro SNP on PC-induced neuroprotection after ischemia. Our results showed that cortical neurons expressing the Pro72-p53 variant exhibited higher PC-mediated neuroprotection as compared with Arg72-p53 neurons. PC prevented ischemia-induced nuclear and cytosolic p53 stabilization in Pro72-p53 neurons. However, PC failed to prevent mitochondrial p53 stabilization, which occurs in Arg72-p53 neurons after ischemia. Furthermore, PC promoted neuroprotection against ischemia by controlling the p53/active caspase-3 pathway in Pro72-p53, but not in Arg72-p53 neurons. Finally, we found that good prognosis associated to TIA within 1 month prior to ischemic stroke was restricted to patients harboring the Pro72 allele. Our findings demonstrate that the Tp53 Arg72Pro SNP controls PC-promoted neuroprotection against a subsequent ischemic insult by modulating mitochondrial p53 stabilization and then modulates TIA-induced ischemic tolerance.

Genome-wide screen for asthma in Puerto Ricans: evidence for association with 5q23 region - Shweta Choudhry; Margaret Taub; Rui Mei; José Rodriguez-Santana; William Rodriguez-Cintron; Mark D. Shriver; Elad Ziv; Neil J. Risch; Esteban González Burchard (Human Genetics, 2008)

FXTAS in Spanish Patients with Ataxia: Support for Female FMR1 Premutation Screening - Laia Rodriguez-Revenga; Beatriz Gómez-Anson; Esteban Muñoz; Dolores Jiménez; Monica Santos; Mar Tintoré; Gisela Martín; Luis Brieva; Montserrat Milà (Molecular Neurobiology, 2007)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Comparison of three methods to estimate genetic ancestry and control for stratification in genetic association studies among admixed populations - Hui-Ju Tsai; Shweta Choudhry; Mariam Naqvi; William Rodriguez-Cintron; Esteban González Burchard; Elad Ziv (Human Genetics, 2005)

Studies on the mechanism of entry of vaccinia virus in animal cells - R. A. Janeczko; J. F. Rodriguez; M. Esteban (Archives of Virology, 1987)